2004
DOI: 10.1080/13682820310001601080
|View full text |Cite
|
Sign up to set email alerts
|

When novel sentences spoken or heard for the first time in the history of the universe are not enough1: toward a dual‐process model of language

Abstract: Although interest in the language sciences was previously focused on newly created sentences, more recently much attention has turned to the importance of formulaic expressions in normal and disordered communication. Also referred to as formulaic expressions and made up of speech formulas, idioms, expletives, serial and memorized speech, slang, sayings, clichés, and conventional expressions, non-propositional language forms a large proportion of every speaker's competence, and may be differentially disturbed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(26 citation statements)
references
References 216 publications
(185 reference statements)
2
24
0
Order By: Relevance
“…This allows for the likelihood that routinized vocal behaviours are managed through a right hemisphere/subcortical circuit with minimal required input from left hemisphere language areas. The dual process model (Wray and Perkins, 2000; Van Lancker Sidtis, 2004; 2006b; 2008) posits that both kinds of language, novel and propositional, are ‘volitionally’ produced using both pyramidal and extrapyr- amidal systems, but that they are stored and processed differently from each other and utilize different cerebral resources. While it has long been observed that the intact left hemisphere can perform all kinds of linguistic processing well, these studies suggest that formulaic language can also be modulated by structures involving intact right hemisphere and/or subcortical nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows for the likelihood that routinized vocal behaviours are managed through a right hemisphere/subcortical circuit with minimal required input from left hemisphere language areas. The dual process model (Wray and Perkins, 2000; Van Lancker Sidtis, 2004; 2006b; 2008) posits that both kinds of language, novel and propositional, are ‘volitionally’ produced using both pyramidal and extrapyr- amidal systems, but that they are stored and processed differently from each other and utilize different cerebral resources. While it has long been observed that the intact left hemisphere can perform all kinds of linguistic processing well, these studies suggest that formulaic language can also be modulated by structures involving intact right hemisphere and/or subcortical nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Conversation includes a characteristic repertory of near-mandatory opening and closing speech formulae (‘how are you’, ‘have a good day’, ‘see you later’). Other formulaic expressions are idioms (‘He spilled the beans’), expletives (‘Oh, heck’), and a rather large array of conventional expressions which can be variously categorized (Wray, 2002; Van Lancker Sidtis, 2004). These differ from novel expressions in that they all have stereotyped form (certain words in a certain order) and conventionalized meanings (social or contextual meanings not strictly derivable from dictionary lexical representations).…”
Section: Introduction and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…The original manual of Melodic Intonation Therapy proposes phrases such as “I love you,” “how are you?” or “thank you” at the lower proficiency level of the program (Helm-Estabrooks et al, 1989). The phrases are stereotyped in form, tied to social context and, therefore, fall into the category of formulaic language (Van Lancker Sidtis, 2004). This fact is critical: according to present knowledge, the production of formulaic language engages bilateral neural networks including right frontotemporal areas, the right basal ganglia and, possibly, the right cerebellum (Hughlings-Jackson, 1878; Speedie et al, 1993; Ackermann et al, 1998; Van Lancker Sidtis et al, 2003; Sidtis et al, 2009).…”
Section: Issue 3: Formulaic Language Resourcesmentioning
confidence: 99%
“…Prodromou, 2008, p. 28). They are closely associated with sociocultural contexts (Kecskes, 2000;Van Lancker Sidtis, 2004). Solidarity or identification with a sociocultural group is signaled by a range of formulaic expressions, especially idioms.…”
Section: The Intertextual Analysismentioning
confidence: 99%